2007
DOI: 10.1063/1.2757335
|View full text |Cite
|
Sign up to set email alerts
|

The activity of the blazar OJ 287 in 2005: XMM-Newton observations and coordinated campaign

Abstract: Two guest-observer XMM-Newton pointings of the blazar OJ 287 in 2005 are introduced, along with part of the radio, mm, near-IR, and optical data obtained during a coordinated and intensive WEBT campaign, during longer-term monitoring observations performed by teams of the ENIGMA network, and during other independent observing programs (like VLBA observations). In that year OJ 287 showed an interesting variable behavior in the optical band. An optical outburst, well matched by our WEBT observations, is claimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 4 publications
(5 reference statements)
4
17
0
Order By: Relevance
“…7, and other XMM-Newton data available are consistent with them. The flux estimated with Swift-XRT is consistent with that of XMM-Newton (Ciprini et al 2007a), but the low statistics due to the short exposure observations Swift does not allow us to look for a possible energy break in the Swift-XRT spectra of OJ 287 (Ciprini et al 2007b;Ciprini et al 2008, in prep.). As shown in Fig.…”
Section: Oj 287supporting
confidence: 56%
“…7, and other XMM-Newton data available are consistent with them. The flux estimated with Swift-XRT is consistent with that of XMM-Newton (Ciprini et al 2007a), but the low statistics due to the short exposure observations Swift does not allow us to look for a possible energy break in the Swift-XRT spectra of OJ 287 (Ciprini et al 2007b;Ciprini et al 2008, in prep.). As shown in Fig.…”
Section: Oj 287supporting
confidence: 56%
“…Wang & Dai (2013) found that X-ray flares from GRBs show SOC behavior. Whether or not SOC characteristics exist in X-ray flares in black hole systems other than GRBs remains unclear, although some hints have been found (Mineshige et al 1994;Takeuchi et al 1995;Negoro et al 1995;Ciprini et al 2003;Zhang 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Such data also corroborated the sub-parsec binary SMBH hypothesis, where optical/UV/X-ray data have evidenced the separation between un-boosted spectral component dominated by thermal bremsstrahlung emission from hot (3 × 10 5 • K) gas and the relativistically beamed in-jet, nonthermal, X-ray emission. The results where obtained thanks to XMM-Newton EPIC and OM observations [1,13,12], and to Swift XRT and UVOT data [14] based on Guest Observer programs and several ToO proposals. The dedicated Swift time-domain experiment is continuing since winter 2015 trough 2016 and 2017 thanks to several observing proposals and ToOs.…”
Section: Some Recent Resultsmentioning
confidence: 99%
“…The optical monitor and multifrequency data obtained with coordinated observing campaigns 2 performed in the years between 2005 and 2008 [1] allowed, in particular, to test the Einstein's General Relativity (GR) theory in strong-field conditions [11] through light curve timing (clocking). Such data also corroborated the sub-parsec binary SMBH hypothesis, where optical/UV/X-ray data have evidenced the separation between un-boosted spectral component dominated by thermal bremsstrahlung emission from hot (3 × 10 5 • K) gas and the relativistically beamed in-jet, nonthermal, X-ray emission.…”
Section: Some Recent Resultsmentioning
confidence: 99%
See 1 more Smart Citation